Trauma in the newsroom: social support, post-traumatic stress and post-traumatic growth among journalists working with terror. Issue 1 (1st January 2019) - Idås, Trond; Backholm, K.; Korhonen, J.
ABSTRACT: Background : Journalists who cover traumatic events are at risk of developing long-term impairment, such as post-traumatic stress disorder (PTSD). The exposure may also result in perceived positive outcomes, conceptualised as post-traumatic growth (PTG). Social support (SS) at work is one factor that might affect the outcome. Objective : To investigate the relationship between three subtypes of workplace SS (perceived support, received support, received recognition), and post-traumatic stress symptoms (PTSS) and between SS and PTG in journalists who have covered a large terror attack. Furthermore, to examine the relationship between ethical dilemmas (ED) experienced while covering the incident, PTSS and PTG. Method : The study was performed as a web-based survey sent out eight to nine months after the incident to Norwegian journalists (N = 375) who covered the terror attack in Norway in 2011. Results : Journalists who received more support also reported a higher level of PTSS (r = .168, p = .044). Recognition and perceived support showed no significant association with PTSS. Journalists who received more recognition also experienced more PTG (r = .542, p < .001). Neither perceived nor received support were significantly associated with PTG. More ED was positively associated with both PTSS (r = .469, p < .001) and PTG (r = .402, p < .001). Conclusions : Journalists with more PTSS may have participated more in organised support such as debriefing activities in the aftermath of the coverage. Some journalists may have experienced stress related to a fear of causing additional harm to first-hand victims (ED). Others may have experienced PTG related to reflections and discussions about their ED in the aftermath of a coverage. Media companies may promote PTG among their journalists by developing a culture for recognition of employees' contributions during demanding missions.